Machine Perfusion of the Liver: A Review of Clinical Trials - Serifis, Nikolaos; Matheson, Rudy; Cloonan, Daniel; Rickert, Charles G.; Markmann, James F.; Coe, Taylor M. (Frontiers in Surgery, 2021)
Although efforts have been made by transplant centers to increase the pool of available livers by extending the criteria of liver acceptance, this practice creates risks for recipients that include primary non-function of the graft, early allograft dysfunction and postoperative complications. Donor liver machine perfusion (MP) is a promising novel strategy that not only decreases cold ischemia time, but also serves as a method of assessing the viability of the graft. In this review, we summarize the data from liver machine perfusion clinical trials and discuss the various techniques available to date as well as future applications of machine perfusion. A variety of approaches have been reported including hypothermic machine perfusion (HMP) and normothermic machine perfusion (NMP); the advantages and disadvantages of each are just now beginning to be resolved. Important in this effort is developing markers of viability with lactate being the most predictive of graft functionality. The advent of machine perfusion has also permitted completely ischemia free transplantation by utilization of in situ NMP showed promising results. Animal studies that focus on defatting steatotic livers via NMP as well as groups that work on regenerating liver tissue ex vivo via MP. The broad incorporation of machine perfusion into routine clinical practice seems incredible.